Validation of MAX-DOAS retrievals of aerosol extinction, SO2, and NO2 through comparison with lidar, sun photometer, active DOAS, and aircraft measurements in the Athabasca oil sands region - Davis, Zoë Y. W.; Frieß, Udo; Strawbridge, Kevin B.; Aggarwaal, Monika; Baray, Sabour; Schnitzler, Elijah G.; Lobo, Akshay; Fioletov, Vitali E.; Abboud, Ihab; McLinden, Chris A.; Whiteway, Jim; Willis, Megan D.; et al. (Atmospheric measurement techniques, 2020)
Abstract. Vertical profiles of aerosols, NO2, and SO2 were retrieved from Multi-Axis Differential Optical Absorption Spectroscopy (MAX-DOAS) measurements at a field site in northern Alberta, Canada, during August and September 2013. The site is approximately 16 km north of two mining operations that are major sources of industrial pollution in the Athabasca oil sands region. Pollution conditions during the study ranged from atmospheric background conditions to heavily polluted with elevated plumes, according to the meteorology. This study aimed to evaluate the performance of the aerosol and trace gas retrievals through comparison with data from a suite of other instruments. Comparisons of aerosol optical depths (AODs) from MAX-DOAS aerosol retrievals, lidar vertical profiles of aerosol extinction, and the AERONET sun photometer indicate good performance by the MAX-DOAS retrievals. These comparisons and modelling of the lidar S ratio highlight the need for accurate knowledge of the temporal variation in the S ratio when comparing MAX-DOAS and lidar data. Comparisons of MAX-DOAS NO2 and SO2 retrievals to Pandora spectral sun photometer vertical column densities (VCDs) and active DOAS mixing ratios indicate good performance of the retrievals, except when vertical profiles of pollutants within the boundary layer varied rapidly, temporally, and spatially. Near-surface retrievals tended to overestimate active DOAS mixing ratios. The MAX-DOAS observed elevated pollution plumes not observed by the active DOAS, highlighting one of the instrument's main advantages. Aircraft measurements of SO2 were used to validate retrieved vertical profiles of SO2. Advantages of the MAX-DOAS instrument include increasing sensitivity towards the surface and the ability to simultaneously retrieve vertical profiles of aerosols and trace gases without requiring additional parameters, such as the S ratio. This complex dataset provided a rare opportunity to evaluate the performance of the MAX-DOAS retrievals under varying atmospheric conditions.
Die 2 in SO2 und NO2 ist tiefgestellt
Gesehen am 16.04.2020